Internationalising the curriculum in business: An overview - Green, W.; Whitsed, Craig (2015)
© 2015 Sense Publishers. All rights reserved. Disciplines are at the heart of the IoC process. Each discipline has its own culture and history, its own ways of investigating, understanding, and responding to the world (Becher, 1989). Differences between disciplines extend far beyond the content taught; they ‘go to the heart of teaching, research and student-faculty relationships’ (Becher & Trowler, 2001, p. 4). Yet, as Hans de Wit and colleagues observe, differing ‘accents and approaches’ to internationalisation shape and are also shaped by local policies, perceptions and practices in different ways; ‘strategies are filtered and contextualized by the specific internal context of the university and their national embeddedness’ (de Wit et al., 2008, p. 7), as much as they are by disciplinary differences. Disciplines are not stable, fixed bodies impervious to change. Like faculties, disciplines are socially constructed communities, comprised of individual academics, each with their own history, culture, sub-disciplinary affiliations, career goals, values and world-view.